Diseño arquitectónico de un Centro Cultural en la parroquia Atahualpa del Cantón Ambato - Meneses Garcés, Yessenia Carolina (2024)
Culture has been present since ancient times, defined as a series of meanings, expectations and commitments shared by a group in society, which order and limit each of the social exchanges and the development of symbols and materials within a space and defined time. The general objective was: to design a Cultural Center for the residents of the Atahualpa parish of the city of Ambato in the period 2023-2024, through strategies with a bioclimatic approach so that it is comfortable for the user. We worked through a mixed research approach with exploratory and descriptive scope. Surveys were administered to parish leaders and surveys to the general population with questions related to culture and cultural activities. The results of the instruments reflected that Atahualpa has a large number of activities, including: dance festivals, entrepreneurship fairs, traditional festivals, end-of-year concerts, contests, games among others. However, they showed the lack of adequate space to carry out cultural activities, since most of them take place in the central park, generating problems with audio, space, crime, disorganization and traffic. Therefore, the proposal focused on the design of an ideal cultural center for the population based on eight architectural and bioclimatic design strategies in order to establish links and develop activities that effectively address the current needs of the community